PENGARUH PELAKSANAAN PROGRAM DANA AMANAH PEMBERDAYAAN MASYARAKAT (DAPM) CISAYONG TERHADAP KESEJAHTERAAN MASYARAKAT DI KECAMATAN CISAYONG KABUPATEN TASIKMALAYA - Fauzy Ridwan, Irwan; Bela Berliana (LPPM IAIT, 2025)
One form of government effort to support this is through the implementation of the Community Empowerment Trust Fund Program (DAPM), which is a community-owned fund derived from the National Program for Community Empowerment (PNPM) funds managed by the community in poverty reduction based on community empowerment, namely through Women's Special Savings and Loan (SPP) activities. This program is designed to provide business capital assistance to underprivileged communities with the hope that they can develop their businesses independently and be able to improve the standard of living of the community. The purpose of this study was to determine the effect of the implementation of the Cisayong DAPM program on community welfare in Cisayong Sub-district, Tasikmalaya Regency. The type of research used is field survey research with quantitative methods. The population in this study were members of the Women's Special Savings and Loan (SPP) which amounted to 157 groups. Researcher sample withdrawal using simple random sampling technique. The method of determining the number of samples using the slovin formula with an accuracy level of 0.1 of the total population obtained a sample of 92 respondents. The results of this study indicate that the T test results state that the Cisayong DAPM program has a significant effect on community welfare. With the coefficient of determination, it can be seen from the R Square of 0.687, which means that the influence of the Cisayong DAPM program variable on community welfare is 68,7% and the rest is caused by other factors.